2008
DOI: 10.1186/1471-2105-9-456
|View full text |Cite
|
Sign up to set email alerts
|

FUNYBASE: a FUNgal phYlogenomic dataBASE

Abstract: Background: The increasing availability of fungal genome sequences provides large numbers of proteins for evolutionary and phylogenetic analyses. However the heterogeneity of data, including the quality of genome annotation and the difficulty of retrieving true orthologs, makes such investigations challenging. The aim of this study was to provide a reliable and integrated resource of orthologous gene families to perform comparative and phylogenetic analyses in fungi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 27 publications
2
59
0
Order By: Relevance
“…The predicted protein sets were searched for highly conserved single-(low) copy genes to assess the completeness of the genomic sequences and gene predictions. Orthologous genes to all 246 single-copy genes were searched for all proteomes by blastp comparisons (eVal: 10-3) against the single-copy families from all 21 species available from the FunyBASE 56 . Additionally, the proteomes were searched for the 248 core genes commonly present in higher eukaryotes (CEGs) by Blastp comparisons (eVal: 10-3) 57 .…”
Section: Methodsmentioning
confidence: 99%
“…The predicted protein sets were searched for highly conserved single-(low) copy genes to assess the completeness of the genomic sequences and gene predictions. Orthologous genes to all 246 single-copy genes were searched for all proteomes by blastp comparisons (eVal: 10-3) against the single-copy families from all 21 species available from the FunyBASE 56 . Additionally, the proteomes were searched for the 248 core genes commonly present in higher eukaryotes (CEGs) by Blastp comparisons (eVal: 10-3) 57 .…”
Section: Methodsmentioning
confidence: 99%
“…All of the 248 CEGs were present in our curated gene set with full HMM domain coverage. On the other hand, FUNYBASE (FUNgal phYlogenomic dataBASE) 17 provides 246 single-copy ortholog clusters in 21 sequenced fungal genomes. We extracted these single-copy protein sequences from the FUNYBASE website and built the HMM model for each cluster.…”
Section: Methodsmentioning
confidence: 99%
“…The protein-coding genes occupy 80% of the genome sequence. According to recently proposed measures for genome completeness, we searched the genome for highly conserved single (or low) copy gene sets: core eukaryotic genes (CEGs) with 248 genes across six model organisms 16 and FUNYBASE 17 with 246 genes with orthologs in 21 fungi. All genes from both gene sets were present in our proteome with full domain coverage.…”
Section: Pichia Pastoris Phylogenetic Positionmentioning
confidence: 99%
“…Sequencing of the highly polymorphic MRR1 gene revealed that group S isolates show more than 4 % divergence from B. cinerea strains B05.10 and T4, which have MRR1 genes with 99.9 % identity. Further sequencing of HSP60 and NEP2, and of two FUNYBASE genes that are suitable for phylogenetic studies (Marthey et al 2008), partially supported the genetic separation of group S isolates (Johnston et al 2013;Leroch et al 2013). Genome sequencing of several B. cinerea and group S strains, and the analysis of additional polymorphic genes in isolates collected from various host plants in different countries, revealed at least two subclades that could be separated from the common B. cinerea genotype (Plesken and Hahn, unpublished).…”
Section: Species Identification and Numbersmentioning
confidence: 99%